Invasive Bacterial Infections of the Musculoskeletal and Central Nervous System during Pig Rearing: Detection Frequencies of Different Pathogens and Specific Streptococcus suis Genotypes - Ninette Natascha Bornemann; Leonie Mayer; Sonia Lacouture; Marcelo Gottschalk; Christoph Georg Baums; Katrin Strutzberg-Minder (Veterinary Sciences, 2024)
Locomotor and central nervous system disorders occur during pig rearing, but there is no systematic recording of the different causative agents in Germany. Joint and meningeal swabs, kidneys, lungs, and eight different lymph nodes per pig were cultured, and isolated pathogens were identified using polymerase chain reactions (PCRs). The cps and pathotype of Streptococcus suis (S. suis) isolates were determined using multiplex-PCR. S. suis was the most important pathogen in the infected joints (70.8%) and meningeal swabs (85.4%) and was most frequently detected in both sites in suckling and weaning piglets. To elucidate the possible portal of entry of S. suis, eight different lymph nodes from 201 pigs were examined in a prospective study. S. suis was detected in all examined lymph nodes (n = 1569), including the mesenteric lymph nodes (15.8%; n = 121/765), with cps 9 (37.2%; n = 147) and cps 2 (24.3%; n = 96) being the most dominating cps types. In piglets with a systemic S. suis infection, different lymph nodes are frequently infected with the invasive S. suis strain, which does not help clarify the portal of entry for S. suis.